Andean worldview in intercultural education - Astorima Farfan , Graciela Milagros (2024)
The Andean worldview could serve as the cornerstone for Peruvian education, as it possesses characteristics vastly different from the Eurocentric conception regarding how to perceive the world, nature, and interact with others. Principles of balance and harmony are ingrained within human actions in both the natural and spiritual habitat. Andean cosmovision upholds harmony with the environment, fostering a mindset of reciprocity, concordance, and complementarity with a relationship of respect between humans and nature. Concepts like allin kawsay (living well) and ayni (mutual aid) would constitute the basic principles of Peruvian intercultural education. Intercultural education must respect ethno-cultural diversity, thereby providing development opportunities for all inhabitants.